The Influence of Accessibility in Financial Reports, Leadership of the Village Head, Community Participation, Competence of Village Officials on the Accountability of Direct Cash Assistance (BLT) - Dapit Harjono; Anisa Kusumawardani (Jurnal Akuntansi, 2025)
This study aims to analyze the influence of Financial Report Accessibility, Village Head Leadership, Community Participation, and Village Apparatus Competence on the accountability of Village Fund Cash Assistance (BLT) management in Bika Hulu Village, Bika District, Kapuas Hulu Regency, West Kalimantan. This study used primary data collected through a questionnaire survey. The research sample was determined using the Slovin formula from a population of 1,001 villagers, resulting in 91 respondents. Data analysis was carried out using the Partial Least Square (PLS) 4.0 method. The results showed that Financial Report Accessibility and Village Head Leadership had a positive and significant effect on the accountability of BLT Village Fund management. Meanwhile, Community Participation and Village Apparatus Competence did not have a significant influence on the accountability of BLT Dana Desa management.